2021
DOI: 10.1016/j.scp.2021.100536
|View full text |Cite
|
Sign up to set email alerts
|

A salt-free and water-saving approach as a green alternative to conventional reactive dyeing of cotton

Abstract: Aqueous reactive dyeing of cotton is considered to be environmentally unfriendly owing to its high consumption of water and salt as well as large discharge of wastewater. However, the industrial applications of current alternative dyeing technologies are difficult to realize due to different problems such as poor dyeing quality, environmental pollution and high cost. Herein, we developed a hydrophobic deep eutectic solvent (HDES) dyeing approach using natural thymol-menthol to overcome the problems caused by r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Pei et al [8] reported the use of a silicon emulsion system for non-aqueous salt-free dyeing of cotton. Wei et al [9] investigated the use of hydrophobic deep eutectic solvent (HDES) composed of thymol and menthol for dyeing of cotton. Attempts have also been made to chemically modify cotton substrates for salt-free dyeing with anionic dyes [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Pei et al [8] reported the use of a silicon emulsion system for non-aqueous salt-free dyeing of cotton. Wei et al [9] investigated the use of hydrophobic deep eutectic solvent (HDES) composed of thymol and menthol for dyeing of cotton. Attempts have also been made to chemically modify cotton substrates for salt-free dyeing with anionic dyes [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The popularity of reactive dyes is mainly due to their high wash fastness and wide colour spectrum [3,4]. Its main disadvantage is that the dyeing process must be carried out in an alkaline medium by adding NaOH or Na 2 CO 3 [2].…”
Section: Introductionmentioning
confidence: 99%